Autistic Children Show a Surprising Relationship between Global Visual Perception, Non-Verbal Intelligence and Visual Parvocellular Function, Not Seen in Typically Developing Children - Brown, Alyse C.; Crewther, David P. (Frontiers in Human Neuroscience, 2017)
Despite much current research into the visual processing style of individuals with Autism Spectrum Disorder (ASD), understanding of the neural mechanisms is lagging, especially with respect to the contributions of the overlapping dichotomies of magnocellular/parvocellular (afferent neural pathways), global/local (perception) and dorsal/ventral (cortical streams). Here, we addressed this deficiency by measuring inspection times (IT) for novel global/local stimuli as well as recording nonlinear visually evoked potentials (VEP), in particular, magnocellular and parvocellular temporal efficiencies. The study was conducted on a group of male ASD children and a typically developing (TD) group matched for mean age and mean non-verbal intelligence, as measured by the Raven’s Progressive Matrices. The IT results did not differ between groups, however a negative correlation between global IT and Raven’s score was found in the ASD group, that was not evident in the TD group. Nonlinear VEP showed the ASD group had smaller amplitude parvocellular-generated second order responses compared to the TD group. This is a sign of improved temporal responsiveness in ASD cf TD groups. Principal Component Analysis linked global IT, non-verbal intelligence scores and VEP parvocellular efficiency in a single factor for the ASD but not the TD group. The results are suggestive of a constraint on pathways available for cognitive response in the ASD group, with temporal processing for those with ASD becoming more reliant on the parvocellular pathway.